AA HUBUNGAN ANTARA KETERLIBATAN PEMBINA, KEMAMPUAN PENGURUS DAN PARTISIPASI ANGGOTA DENGAN KINERJA KEUANGAN KOPONTREN - Abdul Adzim (eBA Journal: Journal Economic, Bussines dan Accounting, 2015)
The objective of this research are to know: 1) the relationship between counselor involvement, management capability, members participation to the financial performance of the Kopontren; 2) the relationship between management capability to the members participation and the relationship between management capability to the financial performance of the Kopontren; 3) the relationship between members participation to the financial performance of the Kopontren. This research was carried out using survey method and taking the primary and secondary data. The primary data were taken from the respondent of 12 counselors from the sample of 12 Kopontren, 36 members of management. The data of members participation were taken using secondary data. The result of this research shows that: 1) the counselor involvement, the management capability and the members participation are together related to the financial performance of the Kopontren; 2) the counselor involvement is related to the management capability, the members participation and the financial performance of the Kopontren; 3) the management capability is related to the members participation, the financial performance. The members participation is related to the financial performance of the Kopontren. The objective of this research are to know: 1) the relationship between counselor involvement, management capability, members participation to the financial performance of the Kopontren; 2) the relationship between management capability to the members participation and the relationship between management capability to the financial performance of the Kopontren; 3) the relationship between members participation to the financial performance of the Kopontren. This research was carried out using survey method and taking the primary and secondary data. The primary data were taken from the respondent of 12 counselors from the sample of 12 Kopontren, 36 members of management. The data of members participation were taken using secondary data. The result of this research shows that: 1) the counselor involvement, the management capability and the members participation are together related to the financial performance of the Kopontren; 2) the counselor involvement is related to the management capability, the members participation and the financial performance of the Kopontren; 3) the management capability is related to the members participation, the financial performance. The members participation is related to the financial performance of the Kopontren.